A novel approach to devise the therapy for ventricular fibrillation by epicardial delivery of lidocaine using active hydraulic ventricular attaching support system: An experimental study in rats. Issue 5 (27th October 2018) - Yasmeen, Sufia; Liao, Xiaoqian; Khan, Farhan Ullah; Ihsan, Awais Ullah; Li, Xue; Li, Cunyu; Chen, Dingding; Yu, Feng; Wang, Zhijie; Sembatya, Kiganda Raymond; Mikrani, Reyaj; Zhou, Xiaohui
Abstract: Active hydraulic ventricular attaching support system (ASD) placed around the heart is not only a novel, nontransplant surgical device used for epicardial administration of drugs like lidocaine, but also a promising treatment option for ventricular fibrillation (VF) and arrhythmias. We hypothesize that lidocaine in 5 mg/kg dose released by ASD significantly improves the VF in the rat model. Sprague‐Dawley (SD) rats were selected and were divided into four groups, intravenous injection (IV), epicardial infusion (EI), ASD, and control. ASD group was further divided into four subgroups for different lidocaine doses (i) ASD+A group (10 mg/kg), (ii) ASD+B group (5 mg/kg), (iii) ASD+C group (1 mg/kg), and (iv) ASD+D group (0.1 mg/kg). VF was induced with calcium chloride injection and was confirmed by electrocardiogram (ECG) in all the groups. VF was treated with different doses of lidocaine using different modes of administration. Data were analyzed using the SPSS 19.0 Chi‐square tests and one‐way analysis of variance (ANOVA). The Kaplan–Meier curve for OS was compared to the Logrank test based on the survival time. P < 0.05 was considered as statistically significant. ASD + B group (5 mg/kg) showed significantly reduced sgroup. The time of first sinus rhythm recovered (15.96 ± 21.77 min) and ▵T‐SOD in plasma (−42.02 ± 26.99 U/mL) was significantly different than that of control, IV, and EI groups. ▵T‐SOD in plasma for all ASD‐treated groups was smaller than the control and IV groups. This study proves that ASD with 5 mg/kg lidocaine dose appears as a promising therapeutic platform for treating VF in rats. Furthermore, ASD may also have potential for treating VF or other cardiovascular disease with different therapeutic agents. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1722–1731, 2019.